Kentrung as an Innovative Media for Integrative Language: Improving Writing, Speaking, and Listening Skills of Elementary Students - Nasma Sania; Muhammad Ilyas Nurul Haq; Novita Kurnia Putri; Fanny Eka Saputri; Abdilah Firda Yuliza; Yogi Swaraswati (Educational Psychology Journal, 2024)
Indonesian plays an important role as the main language in daily communication. However, data shows that integrative language learning in primary schools is still less effective, and children often experience difficulties. Therefore, innovations in learning media that consider the psychological aspects of children are needed. This study aims to evaluate the effectiveness of applying kentrung art as an integrative language learning media in improving writing, speaking, and listening skills. The research method used in this research is quasi-experiment with the experimental model of one group pretest-posttest design. The subjects of this study were fifth grade students of SDN 1 Semampir. Data collection techniques were through pretest and posttest questionnaires and assessment rubrics, and analyzed using descriptive analysis and T-test statistical tests. The T-test showed a significant value = 0.001 <0.05, so it can be concluded that there is a significant difference in the results of the pretest and post-test on integrative language skills. The results of this research show that the application of kentrung art can improve integrative language skills, including writing, speaking, and listening skills, in grade V primary school students.